Determination of Air Transportation Sector Business Management: Analysis of Investment, Services, Marketing Management, and Promotion - Rintis Eko Widodo; Mochammad Subagio; Agus Suhendra; Agus Setiawan; Hendrie Prima Kesuma (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to develop hypotheses related to factors that influence business management, especially in the air transportation sector. The approach used in this literature review study is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles published in the period 2020-2025. The technique used in this literature review is Comparative Analysis. The data used in this descriptive qualitative approach comes from previous studies relevant to this study and sourced from academic online media such as Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Q2-Q4 Emerald, Elsevier, Sage, Web of Science, Sinta 2-5 Journal, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books. The results of this literature review are: 1) Investment affects the business management of companies in the air transportation sector; 2) Services affect the business management of companies in the air transportation sector; 3) Marketing management affects the business management of companies in the air transportation sector; and 4) Promotion affects the business management of companies in the air transportation sector.